Research on the Application of AIGC Technology in Digital Arts Education in Colleges and Universities - Xiang, Xin; Xiong, Yixuan (Journal of Exploration of Vocational Education, 2025)
Abstract: With the rapid development of computer technology, digital arts have transformed from traditional modes towards intelligence and automation. The rise of AIGC (Artificial Intelligence Generated Content) technology has provided new tools and platforms for digital arts education, significantly altering teaching models and talent cultivation strategies. This study aims to explore how colleges and universities can adapt to the development trends of AIGC technology to cultivate digital arts talents suitable for the new era. Through diversified research methods such as literature review, case analysis, interviews, and questionnaires, this study deeply analyzes application instances of AIGC technology in digital arts education, revealing its teaching effects and influences. It provides strategic suggestions for constructing a digital arts curriculum system and teaching model oriented towards future industries.